The pedagogy of traditionalism in győrújbarát (Training and Practice : Journal of Educational Sciences, 2018)
In Győrújbarát there are 10 groups at nursery school. Kindergarten teachers use a special pedagogical programme in their professional practice. They give priority to traditionalism.Paying attention to traditionalism also plays a very important role in everyday life of the groups. Within the framework of projects children learn how to make dishes which were popular in the past or they get to know the tools of the old farms. They also can learn about thefolk dance, music and the national costumes of several regions of our country. If children grow strong roots at a very early age, they will have a massive basis and whatever strong storm comes, they will be able to resist everything.